The roles of micro- and nanoscale materials in cell-engineering systems - Jiang, Yuan; Harberts, Jann; Assadi, Artin; Chen, Yaping; Spatz, Joachim P.; Duan, Wei; Nisbet, David R.; Voelcker, Nicolas H.; Elnathan, Roey (Advanced materials, 2024)
Customizable manufacturing of ex vivo cell engineering is driven by the need for innovations in the biomedical field and holds substantial potential for addressing current therapeutic challenges; but it is still only in its infancy. Micro- and nanoscale-engineered materials are increasingly used to control core cell-level functions in cellular engineering. By reprogramming or redirecting targeted cells for extremely precise functions, these advanced materials offer new possibilities. This influences the modularity of cell reprogramming and reengineering, making these materials part of versatile and emerging technologies. Here, the roles of micro- and nanoscale materials in cell engineering are highlighted, demonstrating how they can be adaptively controlled to regulate cellular reprogramming and core cell-level functions, including differentiation, proliferation, adhesion, user-defined gene expression, and epigenetic changes. The current reprogramming routes used to achieve pluripotency from somatic cells and the significant potential of induced pluripotent stem cell technology for translational biomedical research are covered. Recent advances in nonviral intracellular delivery modalities for cell reprogramming and their constraints are evaluated. This paper focuses on emerging physical and combinatorial approaches of intracellular delivery for cell engineering, revealing the capabilities and limitations of these routes. It is showcased how these programmable materials are continually being explored as customizable tools for inducing biophysical stimulation. Harnessing the power of micro- and nanoscale-engineered materials will be a step change in the design of cell engineering, producing a suite of powerful tools for addressing potential future challenges in therapeutic cell engineering.
Online verfügbar: 14. Oktober 2024
Gesehen am 15.04.2025